Experimental Study on Power Generation Performance of Small Helical Vertical Axis Wind Turbines (HVAWT) - สมัครสมาน, เกียรติศักดิ์; อัศวเทศานุภาพ, ชาญณรงค์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This experimental research aims to evaluate the power generation performance of a helical vertical axis wind turbine (HVAWT) under low wind speed conditions, with a swept area of 0.4 m². The methodology is as follows: the wind turbine was tested in a wind tunnel at wind speeds ranging from 3 to 10 m/s. The shaft torque was measured using a digital torque wrench to record the maximum torque in Newton-meters (Nm), and the wind speed was monitored using a 3-cup anemometer (m/s). The independent variable was the wind speed (3–10 m/s), while the dependent variables included the rotor speed (RPM) and the turbine shaft torque (Nm). The research results are as follows: 1) The wind turbine generated mechanical power ranging from 2.1 W to 47.2 W, which corresponds to an electrical power output of 1.89 W to 42.47 W (assuming a generator efficiency of 0.9). 2) The power coefficient (Cp) ranged between 0.19 and 0.33. 3) The Tip Speed Ratio (TSR) was found to be between 0.99 and 1.30. 4) The turbine achieved its maximum efficiency at a wind speed of 7 m/s, with a power coefficient of approximately 0.33. Additionally, it was found that the wind speed range between 5 and 7 m/s represents the optimal operating range for efficiency. This helical vertical axis wind turbine (HVAWT) outperformed the conventional Savonius VAWT. The robust performance at a low Tip Speed Ratio (TSR) also results in minimal noise emissions during operation. These advantageous characteristics allow for versatile applications in various environments, such as industrial exhaust systems, large-scale building ventilation, high-rise building rooftops, and maritime applications (vessels).